COMMUNITY AWARENESS DURING THE PANDEMIC OF COVID-19: PLASTIC WASTE AS AN ALTERNATIVE ENERGY - Andry Prima; Samsol; Abdul Hamid; Imam Setiaji Ronoatmojo; Heru P Sanusi (Universitas Trisakti, 2022)
The increasingly hoarding volume of plastic waste has attracted numerous researchers to conduct studies in finding the blessing in disguise behind such unpleasant conditions. On the other hand, plastic is one of the end product derived from the refining process of crude or known as petroleum. Thus, the silver lining then can explain the connection between plastic waste and the possibility to use it as alternative energy. By utilizing plastic waste as alternative energy that can substitute the use of conventional fuel, the stage in which people will have a more economical source of energy. As such conditions are established, the economy at the micro or household level will significantly improve. This particular community service reached out to residents of relatively small neighboring houses in Kebun Jeruk Area, Jakarta, Indonesia. During the service, the activity was aimed to provide counseling and training for the community to empower the community on how to make use of plastic waste and process it into an alternative fuel. In the end, such alternative energy should help reduce dependency on the conventional fuel consumed regularly by the household.